Respiratory Syncytial Virus Infection in High-risk Infants – an Update on Palivizumab Prophylaxis - Resch, Bernhard (Bentham Open, 2014)
Morbidity due to respiratory syncytial virus (RSV) disease is still high in infants and children worldwide during the first two to five years of life. Certain categories of high-risk infants with increased morbidity and mortality attributed to RSV disease have been identified and are included in national recommendations for prophylaxis with the monoclonal RSV antibody palivizumab. Most guidelines recommend palivizumab for preterm infants born less than or equal to 32 weeks gestational age with or without bronchopulmonary dysplasia, those born between 33 and 35 weeks gestational age with additional risk factors, and infants and children with hemodynamically significant congenital heart disease. Over the last years several rare diseases have been identified demonstrating high morbidity associated with RSV disease, thus, extension of guidelines for the prophylaxis with palivizumab for these patients with rare diseases including children with malignancy, congenital and acquired immune deficiency, Down syndrome, neuromuscular impairment, cystic fibrosis, congenital diaphragmatic hernia and other severe respiratory disease is increasingly discussed. Efficacy of palivizumab prophylaxis is documented by meta-analysis, and different economic analyses demonstrate cost-effectiveness of palivizumab for the most common indications during the first RSV season.